EXCEPTED BODIES THE TRANSGRESSION OF THE BINARY AND THE FLUX OF NEW PRACTICES - Perrig, Sara (2013)
Referring to what Giorgio Agamben defines in his theory as exception, we can say that the subject of feminism in which Teresa de Lauretis places her accent, is all that allows both the continuity and the suspension of the binary categories of gender. It is in accordance to the interpretation of the lesbic/s subjetc/s as a possibility of both reaffirmation and distortion of binary sexualities, that the opening and the step into new moods and sexual practises among women are done.